Automotive transmissions : fundamentals, selection, design, and application - Naunheimer, Harald , 1963- (Springer, 2011)
This book gives a full account of the development process for automotive transmissions. It covers manual, automated manual and automatic transmissions as well as continuously variable transmissions and hybrid drives for passenger cars and commercial vehicles